Long-Term Administration of Nicotinamide Mononucleotide Mitigates Age-Associated Physiological Decline in Mice - Mills, Kathryn F.; Yoshida, Shohei; Stein, Liana R.; Grozio, Alessia; Kubota, Shunsuke; Sasaki, Yo; Redpath, Philip; Migaud, Marie E.; Apte, Rajendra S.; Uchida, Koji; Yoshino, Jun; Imai, Shin-ichiro (Cell metabolism, 2016)
NAD+ availability decreases with age and in certain disease conditions. Nicotinamide mononucleotide (NMN), a key NAD+ intermediate, has been shown to enhance NAD+ biosynthesis and ameliorate various pathologies in mouse disease models. In this study, we conducted a 12-month-long NMN administration to regular chow-fed wild-type C57BL/6N mice during their normal aging. Orally administered NMN was quickly utilized to synthesize NAD+ in tissues. Remarkably, NMN effectively mitigates age-associated physiological decline in mice. Without any obvious toxicity or deleterious effects, NMN suppressed age-associated body weight gain, enhanced energy metabolism, promoted physical activity, improved insulin sensitivity and plasma lipid profile, and ameliorated eye function and other pathophysiologies. Consistent with these phenotypes, NMN prevented age-associated gene expression changes in key metabolic organs and enhanced mitochondrial oxidative metabolism and mitonuclear protein imbalance in skeletal muscle. These effects of NMN highlight the preventive and therapeutic potential of NAD+ intermediates as effective anti-aging interventions in humans. [Display omitted] •NMN suppresses age-associated body weight gain and enhances energy metabolism•NMN improves insulin sensitivity, eye function, and other features with no toxicity•NMN prevents age-associated gene expression changes in a tissue-specific manner•NMN is an effective anti-aging intervention that could be translated to humans Mills et al. conducted a 12-month-long administration of nicotinamide mononucleotide (NMN), a key natural NAD+ intermediate, to normal wild-type mice, demonstrating that NMN effectively mitigates age-associated physiological decline in mice without any obvious toxicity. These results highlight the significant potential of NMN as an effective anti-aging intervention in humans.